Analysis The Effect Fluctuation of World Oil Price, The Amount of Money Circulation, Inflation, on Gross Domestic Product Period 2000-2020 - Denata, Vigita Liliyawati; Setyowati, Eni; Supriyani, Yustika (Prosiding University Research Colloquium, 2022)
Observations in this study aim at world oil, money supply, and inflation on Gross Domestic Product. The research uses multiple regression method using Eviews 10 software. From the results of the study it can be concluded that partially the money supply and inflation variables are positive and relevant to gross domestic product, while the world oil price variable has a positive but not significant effect on gross domestic product. While the simultaneous effect on the variables of World Oil Prices, Money Supply and Inflation, is significant at 75.04% on gross domestic product, and the remaining 24.96% is influenced by other factors not included in the model. The results of this study continue previous research which is very interesting for further research. This research is expected to be a consideration for policy making for the central government, especially local governments in increasing gross domestic product so that the Indonesian economy remains stable every year.